Comparing Management Strategies for Thoracolumbar Injury Classification and Severity Score of 4 (TLICS = 4) in the Pediatric Population: A Single-Institutional Experience - Jose Castillo; Michael Nhien Le; Khadija Soufi; James Zhou; Edwin Kulubya; Anzhela Moskalik; Yashar Javidan; Julius O. Ebinu (Children, 2024)
Background: Thoracolumbar (TL) fractures are uncommon injuries in the pediatric population. Surgery is recommended for TL fractures with significant deformity, posterior ligamentous complex disruption, or neurological compromise. The Thoracolumbar Injury Classification and Severity Scale (TLICS) has been validated in pediatric populations and serves as a valuable tool for guiding treatment decisions. However, there remains a lack of clarity regarding the appropriate treatment for patients with a TLICS of 4. While conservative and surgical techniques have been described, most studies focused on adult populations, and there is no consensus on the appropriate management in the pediatric population. We reviewed our institutional experience of TL fractures in young children with TLICS of 4, managed both non-operatively and operatively. Methods: A retrospective review of a single institution’s experience managing pediatric patients (<18 years old) with TL fractures receiving a TLICS of 4 from 2015 to 2023 was conducted to determine the clinical outcomes following non-operative and operative treatment. Results: Among 11 pediatric patients, 4 were managed with bracing alone, primarily for posterior column fractures, using a thoracolumbar sacral orthosis (TLSO). Four patients underwent minimally invasive screw fixation (MISF), for Chance or posterior column fractures, with an average operative time of 143 min, blood loss of 29 cc, length of stay (LOS) of 9.8 days, and a follow-up interval of 6 months. Three patients received open posterior screw fixation (OPSF), most commonly for Chance fractures, with averages of 129 min operative time, 225 cc blood loss, 9.7 days LOS, and 4 months follow-up. Both MISF and OPSF utilized intra-operative imaging, with lower radiation exposure in the MISF group. One MISF patients had hardware failure evident by screw lucency on follow-up imaging. Conclusions: Bracing and surgery are safe management options for pediatric TL fractures receiving a TLICS of 4. MISF is an effective alternative treatment strategy, comparable to OPSF, with the advantage of reduced blood loss and radiation exposure. Further studies with age-matched cohorts and long-term outcomes may help determine the optimal management course.